Réponses

2013-12-09T11:25:02+01:00
A = a/b+c 
A = -1/(1/3)+(2/5)
A = -1*3+(2/5)
A = -3+(2/5)
A = -(15/5)+(2/5)
A = -13/5

B = a+b/c 
B = -1+(1/3)/(2/5)
B = -1+(1/3)*(5/2)
B = -1+(5/6)
B = -(6/6)+(5/6)
B = -1/6

C = a/(b+c)
C = -1/((1/3)+(2/5))
C = -1/((5/15)+(6/15))
C = -1/(11/15)
C = -1*(15/11)
C = -15/11
Meilleure réponse !
2013-12-09T11:58:12+01:00
A=(a/b)+c
A=(-1/1/3)+2/5
A=(-1x3)+2/5
A=-3+2/5=-15/5+2/5=-13/5

B=(a+b)/c
B=(-1+1/3)/2/5
B=(-3/3+1/3)/2/5
B=-2/3/2/5=-2/3x5/2=-10/6

C=a/(b+c)
C=-1/(1/3+2/5)
C=-1/(5/15+6/15)
C=-1/11/15=-1x15/11=-15/11